2015
DOI: 10.1016/j.powtec.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of poly(ethylene glycol) in an Inconel 718 feedstock in the metal injection moulding process

Abstract: The degradation and stability of polymer binders in feedstock for metal injection moulding (MIM) have been rarely investigated. Feedstock is a mixture of polymer constituents and metallic powder and is subject to variations in temperature and the complexity of its mechanical effects. The mixture is pressed and squeezed in a mixer with two counter-rotating screws and injected into the mould cavities. This paper investigates the degradation and stability of polymer constituents under the conditions of mixing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…In both HPE and NOHM-I-HPE cases, the majority of the FTIR spectrum remained unchanged upon exposure to oxidative thermal degradation conditions. This is consistent with the literature, because it has been shown that PEO 83 and PEG 84 polymers undergo random chain scission degradation reactions, where some of the chains are broken down until they are small enough to be volatilized. It is common for the remaining liquid residue to possess a composition very similar to the starting polymer, 83,84 as was observed in this study.…”
Section: Elucidation Of Thermal Degradation Mechanisms Of Hpe and Noh...supporting
confidence: 92%
See 1 more Smart Citation
“…In both HPE and NOHM-I-HPE cases, the majority of the FTIR spectrum remained unchanged upon exposure to oxidative thermal degradation conditions. This is consistent with the literature, because it has been shown that PEO 83 and PEG 84 polymers undergo random chain scission degradation reactions, where some of the chains are broken down until they are small enough to be volatilized. It is common for the remaining liquid residue to possess a composition very similar to the starting polymer, 83,84 as was observed in this study.…”
Section: Elucidation Of Thermal Degradation Mechanisms Of Hpe and Noh...supporting
confidence: 92%
“…The characteristic peaks of the FTIR spectra relevant to the oxidative thermal degradation were found in the range of 1400–1900 cm –1 . Figure shows the FTIR spectra of the liquid residue of HPE and NOHM-I-HPE collected after being exposed to air at 120, 140, 160, and 180 °C for 1 h. In comparison to the starting samples, both liquid residues of HPE and NOHM-I-HPE exhibited the appearance of a peak at about 1720 cm –1 , which is consistent with carbonyl stretching and expected for a PEO polymer subjected to heat and an oxygen-containing atmosphere. , Additionally, the HPE samples thermally degraded in air exhibited another peak at about 1680 cm –1 , while the liquid residue from NOHM-I-HPE did not. This peak corresponds to carbonyl stretching, specifically from a free primary or secondary amide. , This suggests that the amine-terminated end of the HPE polymer could be “protected” or “shielded” from oxidative thermal degradation in the case of NOHM-I-HPE as a result of its ionic bonding with the linker molecule staying intact (confirmed by the small peaks at about 1635 and 1525 cm –1 ).…”
Section: Resultssupporting
confidence: 58%
“…the feedstock cannot be recycled indefinitely. In fact, Royer et al (2015) proved that a degradation of the water-soluble binder can be expected for prolonged exposures at high temperatures.…”
mentioning
confidence: 99%
“…The mixing stage generally consists of the preparation of high-loading polymers with thermoplastic polymers and spherical metallic powders [3]. The metallic powder volume loading is usually between 58% and 64% in volume for 316L, with a particle size of 16 microns (median diameter) [4]. Furthermore, the process was developed for a large range of material powders, from austenitic and martensitic stainless steels [3] to titanium alloys and pure-grade [5] and nickel-based superalloys [6,7].…”
Section: Introductionmentioning
confidence: 99%